STRATEGI PENGEMBANGAN KABUPATEN/KOTA LAYAK ANAK DI KABUPATEN KEBUMEN TAHUN 2019 - Saputri, Felika Andriani; Erowati, Dewi (Journal of Politic and Government Studies, 2020)
Kebumen District has been given a number of primary rank in the category ofchildren's Worthy Regency (KLA), in 2019 Kabupaten Kebumen increased to the rank of Madya. Due to the increase in the ranking category in the year 2019 in Kebumen district as the child Worthy district, the research conducted by this researcher relates to the strategy used by the District government of Kebumen in Developing Kebumen District as a child-worthy district. This research became interesting to be researched due to the increase in the ranking category obtained by Kebumen District.The research uses qualitative, descriptive research methods, with data collectiontechniques through observation, interviews, and documentation studies. The subject in this research is: the Office of Community Empowerment and village and empowerment of women and child Protection, District DPRD Kebumen, children's Forum district, village head of the temple, head of Adikarso village, SMP N 2 Kebumen, Puskesmas Karanganyar, and society. The result of this research is describing the findings in the field that is in accordance with the strategic plan of community empowerment and village and empowerment of women and child protection of Kebumen district which is an increase in capacity Institutional and capacity building of child-friendly services that increase the establishment of the Village Child Forum, the establishment of child-friendly schools and the establishment of child friendly puskesmas. Its just that the increase is not accompanied by a variety of activities that can make both child-friendly schools, child-friendly puskesmas, and village childrens’s forums continue to be active. This shows that the increase is only a formality to be formed. From the results of this research, increased establishment of a village child forum, the establishment of child-friendly schools and the establishment of child friendly puskesmas should continue to be maximally enhanced not only formalities mere. In addition, there needs to be an effort to increase the amount of budget that is doing cooperation with private parties. Then conduct training for the parties related to KLA.Keywords: strategy, development, District worthy children